Chemical characterization of odour-active volatile compounds during lucuma (Pouteria lucuma) fruit ripening [Caracterización química de los compuestos activos olfativamente durante la maduración de la fruta de lucuma (Pouteria lucuma)] - Inga M. (2019)
Lucuma (Pouteria lucuma) is an important exportation fruit in Peru. In this work, the odour-active volatile changes during fruit ripening were studied by using a sensomics approach (GC-O in combination with GC-MS analyses). The volatile compound extracts from unripe and ripe fruits were obtained by solvent-assisted flavour extraction (SAFE) with dichloromethane. By application of the aroma extract dilution analysis (AEDA) on the ripe fruit extract, 16 odour-active compounds were detected as responsible of sweet, green, and rancid odour-notes, characteristics of this fruit. Based on odour activity value (OAV) calculation, 2,3-butanedione, methional, (Z)-3-hexenal, (E)-2-hexenal, (Z)-?-ocimene, and 3-methyl butanoic acid were identified as key-aroma compounds in this fruit. These compounds were also quantitated in the unripe fruit SAFE extract finding that their amount increased with during the ripening, such contributing to the development of characteristic odour notes. © 2019, © 2019 The Author(s). Published with license by Taylor & Francis Group, LLC.